(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with the ways of semantic derivation in the thematic group of adjectives, denoting the property ‘dry – wet’. The most productive models are those relating to weather and climate; character, behavior and emotions; intensity of a certain property; qualities perceived by other senses. Nonproductive patterns are given.